Persepsi Mahasiswa tentang Gaya Mengajar Dosen dan Fasilitas Belajar Terhadap Motivasi Belajar Mahasiswa Program Sudi Pendidikan Ekonomi STKIP PGRI Sumatera Barat - Sri Wahyuni (Universitas Negeri Padang, 2018)
This study aims to identify and analyze: 1) the perception of students about the style of teaching faculty to student learning motivation Economic Education STKIP PGRI West Sumatra. 2) To determine the motivation of learning facilities for students studying economics education courses STKIP PGRI West Sumatra 3) To Know students' perceptions on faculty teaching styles and learning facilities jointly influence on student learning motivation STKIP PGRI West Sumatra. This study was conducted In economics education courses STKIP PGRI West Sumatra In force 2012. The population in this study as many as 270 people, while the sample in this study as many as 161 people. Results of the study found that: 1) The perception of students about the style of teaching faculty partial effect on learning motivation students education courses economy STKIP PGRI West Sumatra with a coefficient of 0.027 2) Learning Facilities berpengararuh partially on motivation to learn Students STKIP PGRI West Sumatra, with the coefficient of 0.042 3) The perception of students on faculty teaching styles and learning facilities simultaneous effect on student learning motivation STKIP PGRI West Sumatra calculated F value of 1.006. From the results of this study are expected to pay more attention to the style of teaching faculty in the process of learning so that the learning process takes place better interaction with the students so as to increase the motivation of students in the learning process, and the campus can improve campus facilities in supporting the learning process.